Do Oil and Gas Lease Stipulations in the Northwestern Gulf of Mexico Need Expansion to Better Protect Vulnerable Coral Communities? How Low Relief Habitats Support High Coral Biodiversity - Nuttall, Marissa Faye; Hickerson, Emma L.; Blakeway, Raven D.; Schmahl, George P.; Sammarco, Paul W. (Frontiers in Marine Science, 2022)
The continental shelf of the northwestern Gulf of Mexico harbors extensive reefs and banks that support diverse coral reefs and mesophotic communities. Mesophotic communities range in depth from 40 to 200 m and, in this region, foster some of the densest coral forests [aggregations of mesophotic octocoral, antipatharian, and branching stony coral communities] reported in published literature (10.23 ± 9.31 col/m2). The geologic features underlying the exposed substrates that harbor mesophotic communities are targeted for extensive hydrocarbon exploration and extraction, as they often contain oil and/or natural gas. The Bureau of Ocean Energy Management regulates offshore energy development in the United States and is tasked with protecting sensitive biological communities from impacts related to oil and gas activities. This study analyzed alpha and beta diversity of mesophotic coral forests on fourteen topographic banks in the northwestern Gulf of Mexico. The objective of the study was to examine differences in structure and community in relation to lease stipulations established by the Bureau of Ocean and Energy Management. It was determined that dense and diverse mesophotic coral forests and carbonate producers exist in present regulatory zones that prohibit oil and gas activities; however, the coral communities exist in higher densities, diversity, and richness in low relief substrates outside of these regulatory zones. Our findings suggest low relief hard substrates serve as important habitat for mesophotic coral forests; thus, we suggest the expansion of current stipulations should be considered to provide better protection to vulnerable coral communities on low relief features. Furthermore, additional studies to refine the relationship between low relief structures and biodiversity are needed to develop more meaningful habitat definitions to support resource management and improve resource protection in the future.